Approach to the social sustainability of livestock farms - Cournut S.; Balay C.; Servière G.; Chauvat S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The social dimension of farm sustainability is significantly less documented than the economic and environmental ones. Our objective was to design a framework to analyze it, taking its subjective and context dependent nature into account. The social sustainability was thereby defined from the expression of actors and farmers interviewed in four French contrasted territories, two of which dealt with sheep farming. The different facets of social sustainability identified were organized in seven main axes. The first four are related to farm-focused sustainability: job meaning, work organization, quality of life and health. The last three take into account the embeddedness of farms in a territory and a society: territorial and societal conditions, local and social networks, and contribution to social sustainability of the territory. Our study enlightened the complexity of the social sustainability which refers to different interlocking organization scales (farmers, associates, employees, family, farm, territory), articulates facts and actors’ feelings and expectations, deals with both professional and private lives, and relates to the farm’s situation.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)